TINJAUAN MAKNA BENTUK DAN HIASAN VIHARA DHANAGUN BOGOR - Helsa Fadilah; Muktiono, Ayub (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
The history of the development of architecture in West Java, especially the city of Bogor, is very much influencedby several cultures of other countries. Chinese culture has inherited the heterogeneity of unique and philosophicaloriental architectural decorations. This design style can be found in the design of residential and worship buildings, oneof which is the space in the Dhanagun Temple building which is filled with a variety of ornaments that have very sacredphilosophical and religious values. Research on the object of this building aims to examine the various ornaments andsymbolic meanings contained in the Dhanagun Temple and the architectural styles in every corner of the building.Dhanagun Temple has the characteristics of Chinese architecture. The frame uses a multilevel beam structuralsystem and a beam bond structure system. The shape of the roof stands out with a frame structure system made of wood.This monastery is decorated with ornaments that can be grouped into five categories, namely animals (fauna), plants(flora), nature (universes such as fire, water and sun), geometric, and legends, especially about gods. From the results ofthis study is expected